PENERAPAN AKUNTANSI LINGKUNGAN PADA BADAN USAHA MILIK DESA UNTUK MEWUJUDKAN GREEN ACCOUNTING (STUDI KASUS PADA BADAN USAHA MILIK DESA “X”) - Rizky Wulandari; Dina Natasari; Ihda Arifin Faiz (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2019)
Abstract Village Owned Enterprises (BUMDes) is one of the village entities which foundation aims to improve village welfare through the optimization of village resources. BUMDes in its operations is expected to show social responsibility to the community. One of the social responsibilities is to apply environmental accounting. Environmental accounting means that accounting as a source of management's responsibility information to stakeholders which also provide information about the impact of business processes entity to the surrounding environment. Information on the environmental impacts disclosed in the financial statements which are referred to as Green Accounting. This research aims to analyze the application of environmental accounting on BUMDes